Carbon Sequestration and Storage by Gainesville’s Urban Forest - Francisco Escobedo; Jennifer A. Seitz; Wayne Zipperer (EDIS)
Cities are a major source of carbon dioxide emissions. This fact sheet demonstrates that urban and natural trees can help mitigate the effects of climate change somewhat by sequestering CO2 but can only sequester a small portion of all carbon dioxide emitted from cities. In addition, decomposing trees and mulch, tree maintenance activities, and improperly placed trees that cause shading in winter can also result in emissions of CO2, so it is important for communities to reduce fossil fuel emissions and manage for and preserve large, healthy trees to maximize the amount of CO2 sequestered by an urban forest. This revised 3-page fact sheet was written by Francisco Escobedo, Jennifer A. Seitz, and Wayne Zipperer, and published by the UF Department of School of Forest Resources and Conservation, February 2012.